Informasi Akuntansi Terkait Profitabilitas dan Biaya Monitoring untuk Keputusan Investor Perusahaan Healthcare dan Food and Beverage di Masa Pandemi Covid - 19 - Miati Hana Pertiwi; Aisyaturrahmi (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This research was conducted with the aim of determining the effect of ROA (Return On Asset) and NPM (Net Profit Margin) on stock price with capital structure as an intervening variable with the aim of providing accounting information to investors in making stock price buying and selling decisions. In this study, the population used was companies in the Healthcare sector and the Food and Beverage sub-sector registered on the IDX in 2020-2022. To test the hypothesis in this study, Multiple Regression Analysis was used and continued with Path Analysis to test intervening variables.The research results show that partial ROA has a negative influence on capital structure, while partial NPM has no influence on capital structure. In the second equation, ROA partially has a positive influence on stock price, NPM has a positive influence on stock price and capital structure has a negative influence on stock price. Indirectly, ROA has a significant effect on stock price through capital structure as an intervening variable, while indirectly NPM has no significant effect on stock price through capital structure as an intervening variable.